PENERAPAN SERTIFIKASI HALAL MENURUT UU NOMOR 33 TAHUN 2014 TENTANG JAMINAN PRODUK HALAL : Studi Kasus Pelaku Usaha ‘D’star Crepes di Kota Palopo - Abmi, Musdhalika; Fachrurrazy, Muhammad; Hasan, Hamsah (Universitas Mathla’ul Anwar Banten, 2024)
Purpose this thesis aims to determine the application of halal certification practices according to Law Number 33 of 2014 concerning JPH for D'star Krepes business actors in the city of Palopo; to find out what factors hinder the implementation of halal certification practices according for D'star Krepes business actors in the city of Palopo. Method: The type of research used in this research is empirical research with an empirical juridical approach. Empirical jurisprudence in this research is analyzing phenomena that occur in the field based on applicable laws. The data sources used are primary data, namely Mrs. Mirnawati who is the business owner and main source in the research, and secondary data in the form of official documents, journals, articles and so on. Data collection techniques in this research are observation, interviews and documentation. Data management techniques are editing and organizing. Results and Discussion: The results of this research show that: the implementation of halal certification according to Law Number 33 of 2014 concerning JPH for D'star Krepes business actors in the city of Palopo has implemented halal certification practices in accordance with the JPH Law. Which consists of the obligation to produce halal products, requirements for submitting applications for halal certification, and PPH (Halal Product Process). So the D'star Krepes business actor has succeeded in certifying his business product. However, D'star Krepes business actors have not been able to apply the halal label to products that have been certified halal. The factor that hinders the implementation of halal certification for both business actors and PPH assistants is the network, because registration for halal certification is carried out using the self-declaration method which is done online.